Matlab Use For Teaching And Learning Of Linear Equations Solution With Geometric Approach For Engineering - Rosales Ordoñez, German Raúl (Ingeniería Solidaria, 2011)
Regarding the research work “Use of Matlab for teaching and learning of linear algebra with engineering students from the Universidad de Caldas”, research endorsed by the Vice-rectory of Research from this university, different activities were planned with the purpose of increasing the academic performance and improving linear algebra’s learning (second semester’s engineering subject). To reach this objective, the design and development of an innovative methodology based on laboratory exercises was proposed for each one linear algebra’s topics, by means of mathematical software. The article explains the design of the laboratory “Solution of systems of linear equations using Matlab”.